De la performance à la reconnaissance - Fabienne Malbois (Communication)
Chelsea (Bradley) Manning’s trans identity stems from a gender production that can only partially be explained by the performance analytics underpinning the dramaturgical theories of Judith Butler and Harold Garfinkel. Manning’s particular relationship with visibility as a public figure predicates the need for a recognition analytics anchored in Paul Ricœur’s capacitating phenomenology. Examination of three significant events in Chelsea (Bradley) Manning’s life in the Anglo-Saxon public sphere provides an opportunity to observe different modalities of recognition and discuss the assumptions that underlie the theories of Butler and Garfinkel.